The J Girls : a Reality Show - Hurt, Rochelle (Bloomington, Indiana : Indiana University Press : Indiana Review, 2022)
Winner of the 2021 Blue Light Books Prize, Rochelle Hurt's The J Girls: A Reality Show is a tribute to the grit and glitter of millennial girlhood, a testament to its dangers and traumas, and an elegy for adolescent friendships.
End Credits: Beatitudes for Meek Girls -- Acknowledgments -- Credits -- About the Author
Online resource; title from digital title page (viewed on May 11, 2022).
eBooks on EBSCOhost
Keywords: Female friendship -- Fiction; Teenage girls -- Fiction; Amitié féminine -- Romans, nouvelles, etc; Adolescentes -- Romans, nouvelles, etc; Women Authors; Lesbian; FICTION; Coming of Age; Screenplays; PERFORMING ARTS; Love & Erotica; Subjects & Themes; POETRY; Female friendship; Teenage girls; Electronic books; poetry; Fiction; Poetry; Fiction; Poésie.; Romans